Asteroseismology of red giants: From analysing light curves to estimating ages. Issue 8 (30th September 2016) - Davies, G. R.; Miglio, A.
Abstract: Asteroseismology has started to provide constraints on stellar properties that will be essential to accurately reconstruct the history of the Milky Way. Here we look at the information content in data sets representing current and future space missions (CoRoT, Kepler, K2, TESS, and PLATO) for red giant stars. We describe techniques for extracting the information in the frequency power spectrum and apply these techniques to Kepler data sets of different observing length to represent the different space missions. We demonstrate that for KIC 12008916, a low‐luminosity red giant branch star, we can extract useful information from all data sets, and for all but the shortest data set we obtain good constraint on the g‐mode period spacing and core rotation rates. We discuss how the high precision in these parameters will constrain the stellar properties of stellar radius, distance, mass and age. We show that high precision can be achieved in mass and hence age when values of the g‐mode period spacing are available. We caution that tests to establish the accuracy of asteroseismic masses and ages are still "work in progress".